Pharmacologic reversion of Merkel cell carcinoma via CBP/p300 inhibition - Joseph L. Collura; Kuan Cheok Lei; Mitalee Chandra; Thibault Kervarrec; Hyun Jung Park; Mazdak Dalkoohi; Jürgen C. Becker; Yuan Chang; Patrick S. Moore; Masahiro Shuda (Proceedings of the National Academy of Sciences, 2025)
Merkel cell polyomavirus (MCV) T antigen functions as an oncoprotein that drives the transformation of Merkel cell carcinoma (MCC) cells by activating transcription factors involved in cell proliferation. The viral T antigen promoter requires the activity of the cellular coactivator CREB-binding protein (CBP)/p300 for its expression. Inhibition of CBP/p300 with two distinct small-molecule inhibitors suppresses T antigen expression, leading to cell cycle arrest and upregulation of the cell cycle inhibitor p27 Kip1 . This shift promotes neuronal differentiation, associated with neurite outgrowth in MCC cells. RNA sequencing revealed downregulation of genes involved in E2F, Myc, mTORC1 oncogenic signaling, as well as markers of the Merkel cell lineage including Sox2 and Atoh1. Notably, a rare MCC case exhibiting a mixed cellular composition, with loss of T antigen expression and neuroblastic phenotype, showed a transcriptomic profile resembling that of MCC cells treated with CBP/p300 inhibitors. This suggests that similar differentiation processes may contribute to tumor heterogeneity in patients. This study presents the model system enabling reversible switching between a transformed and differentiated cell state in a human cancer using small-molecule treatment.